Case Report: Holistic approach to management of an infant with severe osteogenesis imperfecta in the neonatal intensive care unit - Timila, Dipsal; Mousa, Amna; Gundamraj, Lalitha (Frontiers in Pediatrics, 2025)
BackgroundOsteogenesis Imperfecta (OI) Type II is the most severe and often lethal form of OI, characterized by profound skeletal fragility and perinatal complications, most notably respiratory failure secondary to thoracic deformities and pulmonary hypoplasia. Effective NICU management requires a holistic, family-centered approach combined with comprehensive medical care, and can be particularly challenging in centers with limited experience managing similar conditions. This is further complicated by ethical dilemmas, including decisions regarding the extent of interventions requiring nuanced judgment and continual reassessment of goals of care.Case presentationWe describe a term infant prenatally diagnosed with OI Type II, born to an 18-year-old mother. After prenatal counseling from maternal fetal medicine (MFM) and neonatologist about the poor prognosis, the mother opted to continue the pregnancy. At birth, the baby presented with multiple fractures, severe growth restriction and required noninvasive positive pressure ventilation. Management required balancing medical interventions with family goals, the infant's quality of life, and ethical dilemmas due to the life-limiting prognosis. A holistic approach involved early multidisciplinary collaboration, weekly communication of family goals, and consistent medical updates along with supporting the teen mother and her family through complex decisions. This led to a safe discharge to concurrent hospice care with supplemental oxygen via nasal cannula and a feeding tube, alongside comprehensive specialty follow-up.ConclusionThis case helps expand the scope of what is possible for families facing life-limiting diagnosis. It informs best practices for navigating prognostic uncertainty, guiding ethical decision-making, and promoting holistic support beyond survival metrics. Cases like this advocate for a shift in focus from solely survival to quality of life and help establish thoughtful standards for managing severe skeletal dysplasias within perinatal and neonatal care frameworks.